Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\omega=\sum_j \omega_jdy^j$. We want to show that $d(F^{*}\omega)=F^{*}(d\omega)$, where $F: M \to N$ is a map from manifold $M$ to manifold $N$. Local coordinate systems of $M, N$ are $(y^1, \ldots, y^m), (x^1, \ldots, x^n)$ respectively.


$$F^{*}\omega=\sum_{j,k}\omega_j\frac{\partial y^j}{\partial x^{k}}dx^k,$$

$$d(F^{*}\omega)=\sum_{j,k,i}\frac{\partial ( \omega_j\frac{\partial y^j}{\partial x^k} )}{\partial x^i}dx^i \wedge dx^k = \sum_{j,k,i}\frac{\partial \omega_j}{\partial x^i} \frac{\partial y^j}{\partial x^k} dx^i \wedge dx^k + \sum_{j,k,i} \omega_j \frac{\partial^2 y^j}{\partial x^i \partial x^k} dx^i \wedge dx^k.$$

$$d\omega=\sum_{j,l}\frac{\partial \omega_j}{\partial y^i} dy^l \wedge dy^j,\qquad F^{*}d\omega = \sum_{i,j,k,l} \frac{\partial \omega_j}{\partial y^l}\frac{\partial y^l}{\partial x^i} \frac{\partial y^l}{\partial x^i} dx^i \wedge dx^k = \sum_{i,j,k} \frac{\partial \omega_j}{\partial x^i} \frac{\partial y^l}{\partial x^i} dx^i \wedge dx^k.$$

My question is why $\displaystyle\sum_{j,k,i} \omega_j \frac{\partial^2 y^j}{\partial x^i\; \partial x^k} dx^i \wedge dx^k = 0$? Thank you very much.

share|cite|improve this question
up vote 4 down vote accepted

Hint: $$\frac{\partial^2 y^j}{\partial x^i\partial x^k} = \frac{\partial^2 y^j}{\partial x^k\partial x^i}$$ but $$dx^i \wedge dx^k = - dx^k \wedge dx^i.$$

share|cite|improve this answer

Forget about $j$ for a moment.
The point is that for a twice continuously differentiable function $f$, you have
$$\sum_{k,i} \frac{\partial^2 f}{\partial x^i \partial x^k} dx^{i} \wedge dx^{k} = 0 \quad (*)$$ This results from:
a) Schwarz's lemma $\frac{\partial^2 f}{\partial x^i \partial x^k} =\frac{\partial^2 f}{\partial x^k \partial x^i} $
b) $dx^{i} \wedge dx^{k}=-dx^{k} \wedge dx^{i}$ (for $i\neq k)$
c) $dx^{i} \wedge dx^{i}=0$
and a regrouping of the sum $(*)$ of $n^2$ terms into three partial sums that I'll leave to you.

The sum you are interested in consists in multiplying the zero expression $(*)$ by $\omega_j$ on the left and adding for all $j$: obviously you will still obtain zero.

Warning: Schwarz $\neq$ Schwartz

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.